Nordic Romanticism
XXXVIII, 300 p. 19 illus.
Keywords: Nordic Romanticism: Translation, Transmission, Transformation is an edited collection exploring the varied and complex interactions between national romanticisms in Britain, Denmark, Germany, Norway and Sweden. The collection considers both the reception and influence of Nordic romanticism in Britain and Germany and also the reciprocal impact of British and German romanticism in the Nordic countries. Taken as a whole, the volume suggests that to fully understand the range of these individual national romanticisms we need to see them not as isolated phenomena but rather as participating, via translation and other modes of reception, in a transnational or regional romanticism configured around the idea of a shared cultural inheritance in ‘the North’. Cian Duffy is Professor and Chair of English literature at Lund University, Sweden. Robert W. Rix is Associate Professor of English literature at Copenhagen University, Denmark.